Structure and factorial invariance of the Grit-Original scale and convergent validity of the network with job satisfaction and happiness - Cristian Ramos‐Vera; Juan José Soza-Herrera; Gleni Quispe-Callo; Antonio Serpa‐Barrientos; Yaquelin E. Calizaya-Milla; Jacksaint Saintila (My University, 2023)
Background: The concept of Grit refers to a person's ability to maintain perseverance and passion in the pursuit of long-term objectives. However, research on the applicability of the Grit-Original scale (Grit-O) in the Latin American context is limited. Objective: This instrumental design study aimed to analyze the structure of this scale and its factorial invariance in relation to gender, as well as to examine its convergent validity with job satisfaction and happiness. Methods: A sample of 364 Peruvian workers that were selected through non-probabilistic convenience sampling in 2021. Results: The results of the confirmatory factor analysis showed that the two-dimensional structure of 12 items presented adequate goodness-of-fit indices. Additionally, the instrument is invariant between men and women. Likewise, the convergent relationship between the Grit scale, job satisfaction, and happiness variables was confirmed, which supports the validity of the instrument in the study context. Conclusion: The findings of the study confirm that the GRIT-O is a measure with adequate psychometric properties in the Peruvian context.
Keywords: Grit; Psychology; Happiness; Social psychology; Scale (ratio); Measurement invariance; Convergent validity; Confirmatory factor analysis; Job satisfaction; Goodness of fit; Context (archaeology); Life satisfaction; Predictive validity; Statistics; Psychometrics; Structural equation modeling; Mathematics; Developmental psychology; Biology; Paleontology; Internal consistency; Physics; Quantum mechanics; Grit; Psychology; Happiness; Social psychology; Scale (ratio); Measurement invariance; Convergent validity; Confirmatory factor analysis; Job satisfaction; Goodness of fit; Context (archaeology); Life satisfaction; Predictive validity; Statistics; Psychometrics; Structural equation modeling; Mathematics; Developmental psychology; Social Sciences Psychology Social Psychology Grit, Self-Efficacy, and Motivation; Social Sciences Psychology Clinical Psychology Resilience and Mental Health; Social Sciences Psychology Applied Psychology Optimism, Hope, and Well-being